Comparison of neonatal respiratory morbidity in neonates delivered at term by elective caesarean section with and without antenatal Corticosteroid - Shabnam Tahir, Faiza Iqbal, Saima Jabeen, Asma Nawaz, Zunaira Arshad, Shazia Rasul (Journal of Rawalpindi Medical College, 2022)
Introduction:Performing elective caesarean section prior to 39 completed weeks,it can lead to breathing problems in neonates as compare to those, who are born through caesarean section without antenatal Corticosteroid. WHO recommends the administration of intramuscular corticosteroids either dexamethasone or betamethason (total 24mg in divided doses) in the antenatal period, when there is a risk of preterm birth. The advantages and disadvantages of a similar regimen given after 37 weeksof pregnancy prior to elective caesarean section (LSCS) to prevent respiratory morbidity in a newborn is yet a topic of discussion.In Pakistan still,many clinicians are doing caesarean section at 37 or 38 weeks without antenatal Corticosteroids. The rationale is to emphasize the use of steroidsbefore caesareanat 39 weeks. Objective:To compare neonatal respiratory distress in neonates delivered between 37 --38+6 weeks of gestation by elective caesarean section with and without antenatal Corticosteroid. Study design:Randomized controlled trial. Setting:Department of Gynae & Obstetrics, unit 2, Shalamar Hospital, Lahore. Duration:Six months from 12th September 2018 to 12th March 2019. Materials and Methods:The study included women who were, planned for elective LSCS at 37-38+6 weeks, divided into two groups .The sample size was 140 (70 in each group),recruited by non-probability consécutive sampling. Inclusion criteria were singleton pregnancy, at 37 to 38+6 weeks for elective LSCS due to indications like primi breech, previous caesarian scar/scars, and maternal wish. All eligible participants were allocated to one of the following groups. Group (A) received an injection of dexamethasone 48 to 72 hours before elective LSCS. Group (B), did not receive an injection of dexamethasone. The outcome to be measuredinthis study were the Apgar score at 1& 5 minutes, the incidence of transient tachpnea of the neonate (TTN) and respiratory distress syndrome (RDS) in newborns,and the need for mechanical ventilation among neonates from two different groups. The data was collected and analyzed by SPSS version 20.Descriptive statistic were applied to calculate the mean and SD for age, gestation age & BMI. Student T-test was used to compare the continuous outcome measures. Neonatal respiratory morbidity was compared in two groups by using the chi-square test at the level of significance of 0.05.Results:Mean age in Group-A was 28.12± 5.6 and in Group-B was 28.97± 6.3 years. There was no statistically significant difference in these groups in termsof Body mass index, gestational age at the time of delivery, age of mother, birth weight, Apgar score at 1 and 5 min,and indications for cesarean section. Neonatal respiratory morbidity was higher in Group-B as compared to Group-A (30% vs.12.9%)p-value-0.013. Conclusion:Antenatal dexamethasone administration significantly reduces the respiratory morbidity among neonates delivered at 37 to 38+6by elective cesarean section. But further studies are required to assess the beneficial role of dexamethasone in the reduction of neonatal respiratory morbidity with a large sample size.Keywords:Neonatal respiratory morbidity, transient tachypnea of newborn, elective caesarean section, antenatal corticosteroids.